Contemporary microenterprise concepts and cases - Muñoz, J. Mark S.; Edward Elgar Publishing (Cheltenham : Edward Elgar, 2010)
While there have been numerous books and articles written on the popular topic of 'microfinance', few books have been written on the business model behind it: the 'microenterprise'. Due to its diversity of thought and high quality of chapter contributions, this book is poised to be the book on 'microenterprises'. Contemporary Microenterprise is a collage of the latest research and viewpoints on the subject by recognized academics and experts from around the globe.
1. Introduction / J. Mark Munoz -- 2. Microenterprise start-up : a cross-national comparison / Michael Troilo -- 3. Microenterprises : the interface between entrepreneur and manager / Michelle Ingram Spain -- 4. Microentrepreneurship in a transitional economy : evidence from Vietnam / Mai Thi Thanh Thai and Ho Thuy Ngoc -- 5. Theoretical view on microenterprise entrepreneurial motivators / Scott A. Hipsher -- 6. Creating a typology for the arts and crafts microenterprise / Ian Fillis -- 7. The challenges for tourism microenterprises in the Tiger Leaping Gorge, Southwest China / Sacha Rawlence -- 8. Microfinance and the growth of micro and small enterprises (MSEs) in Sub-Saharan Africa : the case of Faulu Kenya / Fred O. Newa -- 9. Is microcredit compatible with microentrepreneurship? : evidence from Latin American Tienditas / Michael J. Pisani -- 10. Microfinance : assessing its impact on microenterprises / Gwendolyn Tedeschi -- 11. Serving the poor : innovative business models at the base of the pyramid / Jamie Anderson and Martin Kupp -- 12. Micro-global : can Web-enabled microenterprises successfully internationalize? / J. Mark Munoz and Daewon Choi -- 13. Micro-franchising strategies : drawing lessons from franchise literature / J. Mark Munoz, Ilan Alon and Matthew C. Mitchell -- 14. Microfinance-microenterprise relationship : the Malaysian growth experience / Sow Hup Chan -- 15. Microenterprise growth : the case of Dotz in Brazil / Thelma Rocha and Tales Andreassi -- 16. Microenterprise in a free trade era : the case of Indonesia / Tulus T.H. Tambunan -- 17. Social capital and cross-cultural model replication : the case of hand in hand in India and South Africa / Lin Lerpold and Laurence Romani -- 18. Sponsorship practice at the small business level : an applied perspective / J. Terence Zinger and Norm O'Reilly -- 19. Engaging transnational corporations in community microenterprise initiatives in subsidiary operations : the case of TNCs in Tanzania / Aloysius Newenham-Kahindi -- 20. Achieving economic self-sufficiency through microenterprise training : outcome-based evidence from the Center for Women and Enterprise / Colette Dumas -- 21. Microfinance and poverty alleviation : underlying values and assumptions / Laurence Romani and Lin Lerpold -- 22. Microenterprise sustainability : a Philippine perspective / Jeanette Angeline Banzon Madamba -- 23. Conclusion / J. Mark Munoz.
Includes bibliographical references and index.
Keywords: Small business; New business enterprises; Electronic books